Peran Ganda Ibu Rumah Tangga Dalam Meningkatkan Kesejahteraan Keluarga Perspektif Hukum Islam : (Studi Kasus di Industri Usaha Mikro Kecil Menengah (UMKM) Tofatex di Desa Kademangaran Kecamatan Dukuhturi Kabupaten Tegal) - Rifki, Rifki Hanif; Muhammad; Afif, Abdullah (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2025)
This article discusses the debate regarding family support which should be borne by the husband, but in some cases family support is assisted by working housewives. This research method is a case study, namely the researcher goes into the field by extracting data through interviews. The researcher uses a direct question and answer method to samples who work at Tofatex UMKM. Then, from these results, research analyzed them using analysis qualitative, namely by explaining the narratives of the samples using Islamic law. The research results, Islam has tolerated the presence of a housewife who works as long as her work is in harmony with nature and is carried out in accordance with fitnah and can still take care of the household properly. And don’t forget your obligations as a wife and housewife. this kind of thing also happened during the time of the prophet, it was reported that there was a married woman who worked outside the home either for the social benefit of the community or to meet household needs. Islam also justifies a housewife who works outside the home because of a factor. In the view of Islamic law, if the income family’s maintenance is assisted by a wife, it can be a sadaqoh towards her family. Provided that it freely gives the results of his hard work